County Characteristics, 2000-2007 (United States) ([Verlag nicht ermittelbar], 2007)
This file contains an array of county characteristics by which researchers can investigate contextual influences at the county level. Included are population size and the components of population change during 2000-2005 and a wide range of characteristics on or about 2005: (1) population by age, sex, race, and Hispanic origin, (2) labor force size and unemployment, (3) personal income, (4) earnings and employment by industry, (5) land surface form topography, (6) climate, (7) government revenue and expenditures, (8) crimes reported to police, (9) presidential election results (10) housing authorized by building permits, (11) Medicare enrollment, and (12) health profession shortage areas.